2014
DOI: 10.1002/adem.201400033
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Mechanical Effects of Acid and Thermal Treatments of Carbon Fiber

Abstract: This paper presents modification method toward preparing activated structural carbon fibers (CFs) possessing both good electrochemical and mechanical properties. The surface treatment of CFs has been carried out by chemical and chemical-thermal oxidation, and supercapacitors have been fabricated with CF electrodes. Effects of surface treatment on fiber surface characteristics, mechanical properties, and electrochemical performances were investigated. Results show that proper treatment of CF by chemical-thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…As V f increases, however, the material begins to exhibit nonlinear behavior. From the microscopic viewpoint, the results reported above can be attributed to slippage at the interfaces between the fibers and the matrix, where the interfacial bonding strength is generally related to friction and shearing effects . The elastic limit cp1 was the same for all samples, indicating that the fiber/matrix interfaces were the same in all samples and that V f = 15% is simply the maximum value of V f at which the elastic behavior of the matrix continues to dominate for 3‐mm SBFRPs, whereas when V f is above this value (15%), a higher V f results in a greater effect of fiber reinforcement through micro‐slippage and, consequently, a greater nonlinear deformation capacity [Figure (b–d), II, III].…”
Section: Resultsmentioning
confidence: 87%
“…As V f increases, however, the material begins to exhibit nonlinear behavior. From the microscopic viewpoint, the results reported above can be attributed to slippage at the interfaces between the fibers and the matrix, where the interfacial bonding strength is generally related to friction and shearing effects . The elastic limit cp1 was the same for all samples, indicating that the fiber/matrix interfaces were the same in all samples and that V f = 15% is simply the maximum value of V f at which the elastic behavior of the matrix continues to dominate for 3‐mm SBFRPs, whereas when V f is above this value (15%), a higher V f results in a greater effect of fiber reinforcement through micro‐slippage and, consequently, a greater nonlinear deformation capacity [Figure (b–d), II, III].…”
Section: Resultsmentioning
confidence: 87%
“…Our reported values are in line with other studies featuring flexible supercapacitor electrodes with or without active materials, as shown in Figure 7b. Compared to other surface-active methods, the mixed acid treatment method is simpler and more efficient, and we directly use carbon fibers as fiber electrodes, which avoids problems such as the active material falling off the substrate [43][44][45][46][47]. A series of electrochemical tests and characterization show that the CF-N1S3 electrode has an excellent electrochemical performance.…”
Section: Electrochemical Properties Of Carbon Fiber Electrodesmentioning
confidence: 99%
“…[19] To improve electrochemical performance of CF and energy storage density of the CFRPbased structural supercapacitor, it is necessary to tailor CF surface microstructure and surface activity by a series of appropriate treatments. It was reported that the electrochemically active surface area of CF was enlarged by chemical and chemical-thermal oxidation, [20,21] while the improvement of electrochemical performance was undesirable. In addition, some strong alkaline reagents such as potassium hydroxide and sodium hydroxide are also capable to activate CF surface at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Homogeneous polymer electrolyte has been widely used to prepare structural energy storage devices as it can avoid leakage of ionic liquid. [20,31,43] Therefore, homogeneous polymer electrolyte can ensure a clean and uniform surface for energy storage devices, which is conducive to the post-treatment, assembling, and application.…”
Section: Introductionmentioning
confidence: 99%